Strategies to Enhance Carbon Sequestration through Sugarcane Cultivation to Mitigate the Impacts of Climate Change - Kumar, Ajeet; Sinha, S. K.; Singh, A. K. (Current Research Progress in Agricultural Sciences Vol. 1, 2024)
In the face of escalating global climate change, innovative carbon sequestration practices hold promise for mitigating detrimental environmental impacts. This paper explores various strategies to enhance carbon sequestration through sugarcane cultivation, highlighting the crop's potential as a significant carbon sink. We delve into the use of advanced breeding technologies, agronomic practices, soil management, and the conversion of sugarcane biomass into bioenergy and its by-products as tools for optimizing carbon storage. The study also evaluates the beneficial effects of these practices on overall crop productivity, soil health, and biodiversity. An exploration of the socioeconomic impacts of implementing these strategies, including rural development and job creation, is provided. The paper underscores the necessity of policy support, scientific research, and technological advancement to facilitate the effective implementation of these carbon sequestration strategies in sugarcane cultivation, thereby contributing to the broader climate change mitigation efforts. Our findings suggest that with a strategic approach, sugarcane cultivation can play a pivotal role in mitigating the impacts of climate change through enhanced carbon sequestration. Climate change, primarily driven by anthropogenic greenhouse gas (GHG) emissions, presents a pervasive and daunting global challenge. Among the myriad of responses necessary to mitigate its impacts, enhancing carbon sequestration in agricultural systems offers a substantial, yet underexplored opportunity. This study focuses on strategies to enhance carbon sequestration through sugarcane cultivation, leveraging its potential as a significant carbon sink. Sugarcane (Saccharum officinarum L.) is a tropical, perennial grass, cultivated in over 100 countries, mainly for sugar and ethanol production. It is recognized as one of the most efficient crops in converting sunlight into chemical energy, making it a key player in the bioenergy sector. Apart from its bioenergy potential, sugarcane cultivation presents an excellent avenue for carbon sequestration, especially in its extensive aboveground biomass and the soil. A broad range of strategies, from advanced breeding technologies and agronomic practices to soil management and biomass utilization, can be employed to optimize carbon storage in sugarcane cultivation. These practices have the potential to create a positive impact on crop productivity, soil health and biodiversity, presenting a win-win situation for both the environment and agricultural productivity. Simultaneously, these strategies hold socio-economic benefits, including rural development and job creation, further underscoring their importance. However, realizing these opportunities will require comprehensive policy support, significant research input and technological innovation. This chapter aims to provide an in-depth knowledge of carbon sequestration strategies in sugarcane cultivation and explore how they can contribute to the broader efforts in climate change mitigation. As global communities strive towards a sustainable future, sugarcane cultivation, if strategically managed, can play a pivotal role in enhancing carbon sequestration and mitigating climate change impacts. This chapter on enhancing carbon sequestration through sugarcane cultivation to mitigate climate change impacts may be broken down into several sections: Introduction: This section introduces the issue of climate change, the role of agriculture in mitigating its impacts and the potential of sugarcane as a carbon sink. It also outlines the aims and objectives of the study. Background and Literature Review: This section provides an overview of existing research related to carbon sequestration in sugarcane cultivation and the current understanding of its potential in climate change mitigation. Sugarcane Cultivation and Carbon Sequestration: This part delves into the basics of sugarcane cultivation and its inherent capacity for carbon sequestration, including a detailed discussion of sugarcane's aboveground biomass and soil as carbon storage areas. Strategies for Enhancing Carbon Sequestration: Advanced Breeding Technologies: Discusses genetic improvements and the development of sugarcane varieties that have higher carbon sequestration potential. Agronomic Practices: Explores practices like crop rotation, intercropping and precision agriculture that can increase carbon sequestration. Soil Management: Discusses strategies such as organic amendments, cover cropping and conservation tillage aimed at improving soil health and increasing soil carbon storage. Biomass Utilization: Looks at the conversion of sugarcane residues into bioenergy and other products, which can offset fossil fuel emissions. Socio-economic and Environmental Impacts: This section assesses the broader implications of these strategies on rural development, job creation, crop productivity, soil health and biodiversity. Policy and Research Recommendations: This section outlines the necessary policy support, research initiatives, and technological advancements required for the effective implementation of the discussed strategies. Conclusion: The final section summarizes the findings of the study, reiterates the potential of sugarcane cultivation in enhancing carbon sequestration and mitigating climate change impacts and emphasizes the need for further research and policy action in this area.